The Ang-(1–7)/MasR axis ameliorates neuroinflammation in hypothermic traumatic brain injury in mice by modulating phenotypic transformation of microglia - Ye, Dan; Liu, Jiamin; Lin, Long; Hou, Pengwei; Feng, Tianshun; Wang, Shousen (PloS one, 2024)
The Ang-(1–7)/MasR axis is critically involved in treating several diseases; For example, Ang-(1–7) improves inflammatory response and neurological function after traumatic brain injury and inhibits post-inflammatory hypothermia. However, its function in traumatic brain injury (TBI) combined with seawater immersion hypothermia remains unclear. Here, we used a mice model of hypothermic TBI and a BV2 cell model of hypothermic inflammation to investigate whether the Ang-(1–7)/MasR axis is involved in ameliorating hypothermic TBI. Quantitative reverse transcription PCR, western blotting assay, and immunofluorescence assay were performed to confirm microglia polarization and cytokine regulation. Hematoxylin-eosin staining, Nissl staining, and immunohistochemical assay were conducted to assess the extent of hypothermic TBI-induced damage and the ameliorative effect of Ang-(1–7) in mice. An open field experiment and neurological function scoring with two approaches were used to assess the degree of recovery and prognosis in mice. After hypothermic TBI establishment in BV2 cells, the Ang-(1–7)/MasR axis induced phenotypic transformation of microglia from M1 to M2, inhibited IL-6 and IL-1β release, and upregulated IL-4 and IL-10 levels. After hypothermic TBI development in mice, intraperitoneally administered Ang-(1–7) attenuated histological damage and promoted neurological recovery. These findings suggest that hypothermia exacerbates TBI-induced damage and that the Ang-(1–7)/MasR axis can ameliorate hypothermic TBI and directly affect prognosis.